The 2011 Japanese earthquake, tsunami and nuclear crisis: evidence of contagion from international financial markets - Simplice A. Asongu (African Governance and Development Institute (AGDI), 2011)
Purpose Natural disasters may inflict significant damage upon international financial markets. The purpose of this study is to investigate if any contagion effect occurred in the immediate aftermath of the Japanese earthquake, tsunami and subsequent nuclear crisis. Design/methodology/approach Using 33 international stock indices and exchange rates, this paper uses heteroscedasticity biases based on correlation coefficients to examine if any contagion occurred across financial markets after the March 11, 2011 Japanese earthquake, tsunami and nuclear crisis. The sample period is partitioned into two sections: the 12-month pre-earthquake period (March 11, 2010 to March 10, 2011) and the 2-month post-earthquake period (March 11, 2011 to May 10, 2011). While the stability period is defined as the pre-earthquake period, the turbulent (turmoil) period is defined as the post-earthquake period. In a bid to ensure robustness of our findings, the turmoil period is further partitioned into two equal sections: the 1-month (short-term) post-earthquake period (March 11, 2011 to April 10, 2011), and the 2-month (medium-term) post-earthquake (March 11, 2011 to May 10, 2011). Findings Findings reveal that, while no sampled foreign exchange markets suffered from contagion, stock markets of Taiwan, Bahrain, Saudi Arabia and South Africa witnessed a contagion effect. Practical implications Our results have two paramount implications. Firstly, we have confirmed existing consensus that in the face of natural crises that could take an international scale, emerging markets are contagiously affected for the most part. Secondly, the empirical evidence also suggest that international financial market transmissions not only occur during financial crisis; natural disaster effects should not be undermined. Originality/value This paper has shown that the correlation structure of international financial markets are also affected by high profile natural disasters.
Keywords: G10; G15; F30; 330; Japanese Earthquake; Contagion; International Financial Markets